Analisa Yuridis terhadap Pemegang Merek Dagang UMKM Berdasarkan Undang-Undang No.20 Tahun 2016 Tentang Hak Merek dan Indikasi Geografis - Eddy Ramon Torong; Adi Sulistiyono (Universitas Sains dan Teknologi Komputer, 2023)
The legal protection given to trademark certificate holders is that the trademark is valid for a period of 10 years and the only registered trademark owner has the rights to the trademark and cannot be changed without the trademark owner's permission. Law enforcement provided by the Trademark and Geographical Indications Law is criminal and civil. There are other alternatives, namely through arbitration and alternative dispute resolution with the concept of a win - win solution.